Autophagy and Mechanisms of Effective Immunity - Mintern, Justine; Villadangos, Jose A. (Frontiers in Immunology, 2012)
Macroautophagy (autophagy) is a cellular pathway facilitating several critical functions. First, by acting to ensure the degradation of damaged cellular content, autophagy is an important mechanism of intracellular homeostasis. Second, autophagy is a major trafficking pathway, shuttling content between the cytosol and the lysosomal compartment. Given these two key roles, autophagy can have significant and sometimes unexpected consequences on mechanisms that initiate robust immunity. Here, we will discuss the impact of autophagy on pathways of innate and adaptive immune responses including inflammatory cytokine production, antigen processing and T and B lymphocyte immunity.